Improving Light Extraction of Organic Light-Emitting Devices by Attaching Nanostructures with Self-Assembled Photonic Crystal Patterns - Kai-Yu Peng; Da-Hua Wei (International Journal of Photoenergy)
A single-monolayered hexagonal self-assembled photonic crystal (PC) pattern fabricated onto polyethylene terephthalate (PET) films by using simple nanosphere lithography (NSL) method has been demonstrated in this research work. The patterned nanostructures acted as a scattering medium to extract the trapped photons from substrate mode of optical-electronic device for improving the overall external quantum efficiency of the organic light-emitting diodes (OLEDs). With an optimum latex concentration, the distribution of self-assembled polystyrene (PS) nanosphere patterns on PET films can be easily controlled by adjusting the rotation speed of spin-coater. After attaching the PS nanosphere array brightness enhancement film (BEF) sheet as a photonic crystal pattern onto the device, the luminous intensity of OLEDs in the normal viewing direction is 161% higher than the one without any BEF attachment. The electroluminescent (EL) spectrum of OLEDs with PS patterned BEF attachment also showed minor color offset and superior color stabilization characteristics, and thus it possessed the potential applications in all kinds of display technology and solid-state optical-electronic devices.